Cartesian reflections about moral good - Ocampo Giraldo, Rodrigo Jesús (Estudios de Filosofía, 2010)
In addition to the interest that René Descartes had to construct a solid building of knowledge, there flection on morality and the question of how to behave oneself in life, has an equally important place in his philosophy. In various letters and writings oriented to the search for truth, it is possible to trace a number of considerations about what constitutes a moral life oriented in a moral sense by the right use of reason.